Seroprevalence of SARS-CoV-2 in cats from COVID-19 positive households in the Lisbon area - Moutinho, Isa; Cardoso, Sara; Henriques, Mafalda; Gonçalves, João; Tavares, Luís; Gil, Solange; Nunes, Telmo; Aires-da-Silva, Frederico (Frontiers in Veterinary Science, 2025)
IntroductionSince the onset of the COVID-19 pandemic, the transmission of SARS-CoV-2 between humans and cats has been well-documented. However, the dynamics of this cross-species transmission remain insufficiently understood. Seroprevalence studies in cat populations across different contexts and regions are crucial for estimating viral infection rates and tracking viral evolution. Furthermore, identifying risk factors associated with human-to-cat transmission is essential.MethodsThis study, conducted during the COVID-19 pandemic, assessed SARS-CoV-2 transmission and seroprevalence in 76 cats from COVID-19-positive households in the Lisbon area. Antibodies against SARS-CoV-2 variants (alpha, delta and omicron) were detected using enzyme-linked immunosorbent assay (ELISA). Positive samples were further tested for neutralizing antibodies using surrogate virus neutralization test (sVNT) and pseudotyped virus assays. To identify risk factors for human-to-cat SARS-CoV-2 transmission, we analyzed the association between animal characteristics, cat-owner interactions, owner clinical signs and sVNT results.ResultsOf the 76 cats tested, 23 (30.3%) were ELISA-positive for SARS-CoV-2 antibodies. Among these, 16 (69.6%) exhibited potent neutralizing antibodies confirmed via sVNT and pseudotyped virus assays. Compared to our previous study of cats with unknown exposure to SARS-CoV-2 in the Lisbon area, this study found significantly higher rates of seroprevalence (30.3% vs. 14.7%) and neutralizing antibody prevalence (69.6% vs. 20.4%) in cats from COVID-19-positive households. None of the risk factors studied showed a statistically significant association with seropositivity in cats.DiscussionThese findings suggest a greater exposure and infection risk in cats from COVID-19-positive households. The absence of significant associations with the analyzed risk factors highlights the complexity of human-to-cat SARS-CoV-2 transmission. Future studies should further investigate the impact of demographic characteristics, health conditions, lifestyle, owner-cat interactions, and owners’ symptoms during infection to better understand their role in SARS-CoV-2 transmission from humans to cats and to inform strategies for controlling future outbreaks.